Strategies Focused on the Teaching of Programming Logic: A Systematic Review of Brazilian Literature - de Oliveira, Tiago; Stringhini, Denise; Correa, Deborah Godoy Martins (2018 XIII Latin American Conference on Learning Technologies (LACLO), 2018)
This article aims to present the results obtained from the systematic of the Brazilian literature on teaching and learning the discipline of Programming Logic (LP), considering the articles published in the Brazilian Journal of Informatics in Education (RBIE), in the annals of the Brazilian Symposium on Informatics (SBIE), in the annals of the Computer Science Workshops (WIE), in the Brazilian Congress of Informatics in Education (CBIE) and in the Journey of Updating in Computer Science at School (JAIE) between 2012 and 2017. From this mapping the strategies used in teaching LP in Basic Education, High School and Higher Education were analyzed, and was verified that the subject remains a great challenge to be overcome. Additionally, this work investigates if Multiple Intelligences are being considered in the adoption of teaching techniques - the goal is to establish a future work on this subject. Results show that Scratch and Games are the most cited in Brazilian literature and that Multiple Intelligences are still an open research field in this context